Influence of Age and School Type on Reform Practices Performed by School Heads - Bedi, Innocent Kwame; Kukemelk, Hasso (Mediterranean Journal of Social Sciences, 2021)
The purpose of this study is to examine the level of implementing reform practices and their resulting stress and to explore the influence of age, gender, school type and tracking type on performing reform practices and the perceived stress in implementing reforms among school leaders. A quantitative research design was used with respondents sampled from among senior high school heads. The data were analysed using multinomial logistic regression to examine the influence of demographic (age and gender) and school variables (school type and tracking type) on implementing reform and its perceived stressfulness. The findings showed that on implementing reforms and its inherent stressfulness, a majority of school heads ‘always’ perform reform duties and a greater proportion reported high-stress levels in implementing reforms from 'somewhat causes’ stress to ‘causes great’ stress. Regarding demographic and school variables, age was a significant negative predictor of implementing reforms, indicating that younger heads were more likely to perform reform functions than older heads while school type significantly influences stress level in implementing reforms, implying that heads in boarding schools were more likely to experience higher stress levels in implementing reforms than heads in day schools. The authors recommended continuous in-service training for school heads, the practice of distributive leadership style and provision of infrastructure to phase out the double-track (shift system) in some schools.   Received: 4 June 2020 / Accepted: 20 August 2021 / Published: 5 September 2021